Optimizing seedling production for the conservation of the threatened Dyckia rariflora (Bromeliaceae) - Giselly Mota da Silva; Evandro Alves Vieira; Luiz Palhares Neto; Leilane Barbara Gomes; Markus Gastauer; Silvio J. Ramos; Cecílio Frois Caldeira (BMC Research Notes)
Abstract Objectives In vitro seed propagation can enhance plant species growth and enable the rapid production of seedlings while preserving genetic variability. This study aimed to develop in vitro seed propagation and acclimatization protocols for Dyckia rariflora to support conservation efforts of this bromeliad endemic to ferruginous campos rupestres. Seed germination and plant growth were tested using MS (Murashige & Skoog) culture medium with varying salt concentrations, sucrose levels, and the presence or absence of polyvinylpyrrolidone (PVP). Following these treatments, seedlings were acclimatized after removal from the controlled environment. Results Germination rates varied between 65 and 90%, unaffected by treatment. The highest germination speed index was in half MS salts without PVP, while full MS salts, sucrose, and PVP slowed germination. Half MS salts resulted in seedlings with greater height, more leaves, and longer roots. Complete MS salts were less effective. No seed oxidation was observed. After 120 days of acclimatization, survival rates exceeded 70%, with plants in half MS salts and 15 g sucrose showing the best growth. In vitro propagation of D. rariflora is viable for large-scale plant production, with half MS salt and sucrose concentrations, without PVP, recommended for better plant growth and cost reduction.